A DISTRIBUIÇÃO DIAMÉTRICA PARA BRACATINGAIS EM DIFERENTES IDADES, SÍTIOS E DENSIDADES NA REGIÃO METROPOLITANA DE CURITIBA - Bartoszeck, Alexandra Consuelo de Plácido e Silva; Machado, Sebastião do Amaral; Figueiredo Filho, Afonso; Oliveira, Edilson Batista (Floresta, 2004)
Esta pesquisa tem como objetivo estudar o comportamento de funções de densidade probabilística no ajuste de distribuições diamétricas para diferentes idades, sítios e densidades para povoamentos de bracatinga (Mimosa scabrella Benth) localizados nos municípios da Região Metropolitana de Curitiba, PR. Os dados utilizados são provenientes de um experimento delineado em blocos ao acaso, constituído de 5 blocos e 4 tratamentos, perfazendo um total de 20 parcelas, as quais foram remedidas 4 vezes às idades aproximadas de 4, 5, 6 e 7,5 anos de idade. A densidade inicial foi reduzida para 2000, 4000, 8000 árvores por hectare, sendo que as testemunhas não sofreram nenhum tratamento. Desses cinco blocos, um estava localizado na classe de sítio I, dois na classe II e dois na classe III. Paralelamente, foram instaladas e medidas 124 parcelas temporárias, distribuídas nos vários municípios da Região Metropolitana, representando os povoamentos de bracatinga sob o regime tradicional de cultivo e manejo, abrangendo as idades de 3 a 18 anos e as 3 classes de sítio. As seguintes funções de densidade probabilística foram ajustadas para cada combinação de idade, sítio e densidade: Normal, Lognormal, Gama, Beta, Weibull 2 parâmetros, Weibull 3 parâmetros e a SB de Johnson. Através do teste D de Kolmogorov-Smirnov detectou-se que a função SB de Johnson foi a de melhor desempenho para a maioria das combinações de dados, sendo, portanto, a primeira no ranking. Os índices de simetria e curtose indicaram que as curvas de distribuições diamétricas em bracatingais são unimodais, tornando-se cada vez mais assimétricas positivas e mais achatadas com o avanço da idade. DIAMETER DISTRIBUTION FOR STANDS OF Mimosa scabrella FOR DIFFERENT AGES, SITES AND DENSITIES Abstract The objective of this research work was to study the behavior of several probability density functions in fitting the diameter distribution for different ages, sites and densities for stands of bracatinga (Mimosa scabrella Benth) located in the Curitiba metropolitan region. The utilized data came from an initial density trial, designed in random blocks, formed by 5 blocks and 4 treatments, in a total of 20 permanent sample plots with an area of 325 m2, which were remeasured 4 times at approximate ages of 4, 5, 6 and 7,5 years. The initial density was reduced for 2000, 4000, 8000 trees per hectare, remaining the control plots without any reduction of trees. From these five blocks, one was located on site class I, two on site class II and two blocks on site class III. Simultaneously they were also implanted and measured diameters and heights of every tree in 124 temporary sample plots (325 m2) scattered by several counties of the Curitiba metropolitan region, on stands that represent the traditional way of cultivation and management of bracatinga. These plots covered ages from 3 to 18 years and the 3 sites classes. Seven probability density functions were tested to fit the diameter distribution: Normal, Lognormal, Gama, Beta, Weibull 2 parameters, Weibull 3 parameters and the SB from Johnson. The combination of sites, densities and ages for the permanent and the temporary sample plots with these seven functions made it possible to accomplish 434 analysis. The Kolmogorov-Smirnov test was applied for every analysis for the choice of the best function. The Jonhsons SB function was the one that presented the best performance, being so, used for the construction of the diameter distribution curves. The asymmetry and Kurtosis indexes indicated that the curves of diameter distributions in bracatinga stands are unimodal, as hypothesized, becoming more and more asymmetric positively and more flattened as the stands become older.